Impaired cross-talk between NO and hyperpolarization in myoendothelial feedback: a novel therapeutic target in early endothelial dysfunction of metabolic disease. (April 2019) - Alaaeddine, Rana A; Mroueh, Ali; Gust, Stephen; Eid, Ali H; Plane, Frances; El-Yazbi, Ahmed F
Highlights: Myoendothelial feedback is an integrated response combining NO and EDH. Both pathways interplay in a manner that allows mutual facilitation. Metabolic disorders are associated with an impairment of both pathways. Decreased EDH function aggravates endothelial dysfunction by decreasing NO activity. Abstract : Over the past three decades, our view of the endothelium rapidly evolved from a static lining of the blood vessels to a dynamic determinant and regulator of vascular tone and homeostasis. It is now widely accepted that endothelial dysfunction is a hallmark of almost every vascular pathology, either as a cause or a consequence. The tight association between the metabolic disease spectrum, ranging from mild alterations of blood lipids profile all the way to diabetes and morbid obesity; and vascular complications argues for a deleterious endothelial remodeling in these conditions. Extensive research demonstrated endothelial changes in these conditions including reduced endothelial nitric oxide activity, altered response to endothelium-dependent hyperpolarization, and increased production of contractile agents. For the most part, studies investigated different aspects of endothelial function in isolation of each other. In this review, we propose a model of an integrated endothelial response and offer an alternative view for potential dysfunction early in the course of metabolic disease continuum. In such a framework, only slight changes in the expression/function of molecular players in one endothelium-dependent pathway would be sufficient to trigger a cascade of events compromising endothelial function. We will also consider the available data describing the possible effects of intervention with different therapeutic agents on endothelial function early in the course of metabolic disease.